An Invitro Study on Microleakage of Root MTA, Proroot MTA, One Coat Bond and Amalgam in Furcation Perforation Repair - M Bidar; R Disfani; M Charechahi; R Tabatabai (Isfahan University of Medical Sciences, 2007)
Introduction: Furcal perforation is a common accident during endodontic treatment. Prognosis of furcal perforation repair is determined by several factors. One of these factors is sealing ability and biocompatibility of materials used to repair furcal perforation. So far, different materials have been suggested for repair of furcal perforation. One of these materials that based on investigations has shown agreeable properties and clinical success when used as repairing material for furcal perforation, is MTA. Since Proroot MTA is very expensive and not easily accessible for all dentists, we decided to evaluate microleakage of MTA produced in Iran. In this in vitro experiment, sealing abilities of Proroot MTA, Root MTA (Iran-MTA), Amalgam and One coat bond in repairing furcal perforations was compared. Methods and Materials: Furcal perforations as 1 mm diameter defects was created in 60 extracted maxillary and mandibular molars. The teeth were divided into four 15 teeth groups. Each group was sealed with one of the materials. The crowns of teeth were restored by amalgam. Then dye penetration test was done. A longitudinal sectioning was performed. Samples were studied under stereomicroscope and data were analyzed by means of Duncan statistical test. Results: The results showed that no significant difference in sealing ability was found among Proroot MTA, Root MTA (Iran- MTA) and One coat bond (p value > 0.05). But there was a significant difference in sealing ability between Root MTA and Amalgam (p value < 0.05).Conclusion: Root MTA can be an acceptable substitute for Proroot MTA. Key Words: Furcation perforation, Microleakage, Root MTA, Proroot MTA, One coat bond